Experiences of transgender and gender diverse patients in emergency psychiatric settings: A scoping review - Megan O'Brien; Matthew E. Hirschtritt; Peggy Tahir; Raj K. Kalapatapu (Journal of the American College of Emergency Physicians Open)
Abstract Objective This scoping review aims to characterize what is known about transgender and gender diverse (TGD) individuals in emergency psychiatric settings and identify what gaps persist in this literature. Methods A search of 4 electronic databases (PubMed, Web of Science, GenderWatch, and PsycINFO) was used for data collection. Included were studies that looked at TGD individuals presenting to a psychiatric emergency department (ED) or ED with a primary mental health concern. Study screening progress was documented in a Preferred Reporting Items for Systematic reviews and Meta‐Analyses flow chart. A total of 232 titles and abstracts were screened, 38 full texts were evaluated for eligibility, and 10 studies were included. Results The studies reviewed identified mental health vulnerabilities unique to the TGD population, including service denial in health care settings, gender dysphoria, increased rates of non‐suicidal self‐injury, and in some studies an increase in suicidality. Societal inequities, including the risk of discrimination and residential instability, were also revealed. A subset of the studies identified best practices in caring for this population, including the use of non‐judgmental, affirmative, and inclusive language, and on a structural level creating emergency environments that are confidential, inclusive, and therapeutic for these individuals. Conclusions There is limited information on TGD individuals in emergency psychiatric settings, and thus it is difficult to form strong conclusions. However, the current evidence available suggests possible inequities in this population. Three major themes with regards to TGD individuals in emergency psychiatric settings were identified: mental health vulnerabilities, societal inequities, and best practices in caring for this population. Overall, there is a scarcity of literature in this field, and further research on the experiences of this population is needed to inform clinical practice.